The effects of complex training on performance variables in basketball players: a systematic review and meta-analysis - Kambitta Valappil, I. N.; Parpa, K.; Govindasamy, K.; Katanic, B.; Clark, C. C. T.; Elayaraja, M.; Karmakar, D.; Baltean, A. I.; Fort, P. R.; Geanta, V. A. (Frontiers in Sports and Active Living, 2025)
Introduction: Basketball requires explosive power, agility and change of direction (CoD) ability. Although often used interchangeably with agility, CoD is distinct: it involves rapid directional changes in response to a pre-planned stimulus, while agility also requires perceptual cognitive responses to unpredictable cues. In this review agility is considered under CoD, emphasizing the physical component that can be directly trained. Improving CoD and power is essential for optimal basketball performance. Complex training (CT), which combines strength and plyometric exercises, has emerged as a promising method. However, its specific effects on basketball player's physical performance variables remain unclear, warranting a focused systematic review and meta-analysis.